Utilization of Palm Kernel Cake in Muscovy Ducks - Mohammed, Mustafa Fadil (2003)
Four experiments were conducted on Muscovy ducks to evaluate their utilization, performance and nutrient digestibility when offered diets containing different levels of palm kernel cake (PKC). In the first experiment, two types of PKC (solvent and expeller extracted) were force-fed to male and female ducks 7 weeks of age and the nutrient digestibility, true metabolizable energy and true amino acid digestibility were determined. There was no significant (p>0.05) effect on the type of PKC used on crude protein (CP), ether extract (EE), metabolizable energy (ME) and amino acid (AA) digestibility, except for those of dry matter (DM) and neutral detergent fibre (NDF) which was higher in solvent extracted compared to expeller extracted PKC. It was found that the ducks utilized about 47% of the gross energy in PKC. The average apparent metabolizable energy value of PKC for Muscovy ducks was obtained to be 1870 kcal/kg, which was rather higher than those reported in broiler chickens. The performance of male and female Muscovy ducks when fed diets containing 15% and 35% levels of PKC were investigated. The results indicated that inclusion of up to 15% of PKC in growing diet for ducks did not depress growth nor feed conversion ratio (FCR) at any significant degree. Given the low cost of PKC, such usage is likely to be economic, depending, to some extent, on cost of added oil. At this level no negative effect in faecal consistency nor carcass fatness were observed. As PKC level increased up to 35%, the ducks ate more feed and as a result had poorer FCR. The explanation for the poorer FCR could be related to the decline in the energy and protein digestibility when ducks were fed at higher PKC level as compared to the control diet. It could be suggested that addition of oil to PKC based diet may improve the palatability and thus the feed intake and the performance of the ducks. Differences in the feed efficiency and nutrient digestibility between Muscovy ducks and broiler chickens were found when PKC was included up to 25% in the diet. Feeding up to 25% level of PKC to ducks was not associated in any detrimental effects on the performance and FCR. However, FCR was depressed when PKC was added at 25% level to broiler grower diet. The ME value was found to be higher in ducks than in chickens. This indicates that the ME value for chickens cannot be applied to ducks. The digestibility of NDF was found to be higher for ducks than for chickens and this could be due to the higher hemicellulose digestibility for ducks than for chickens.